Emerging corticosteroid delivery platforms for treatment of diabetic macular edema. (1st October 2020) - Shah, Janika; Vaze, Anagha; Tang Lee Say, Timothy; Gillies, Mark C; Fraser-Bell, Samantha
ABSTRACT: Introduction: Diabetic macular edema (DME) is a leading cause of vision impairment. Low-grade inflammation is thought to play a critical role in its pathogenesis. Although vascular endothelial growth factor inhibitors are used first-line, not all eyes with DME respond optimally and may respond better to corticosteroids. Currently corticosteroids for DME are given intravitreally and require regular monitoring. There is an unmet need for longer lasting therapies and/or effective noninvasive therapies such as those given via oral or topical routes. Areas covered: This review discusses emerging corticosteroid delivery platforms for DME treatment. A literature search of investigational novel therapeutic steroid delivery platform in DME was conducted. Results are presented from preclinical, phase 1, 2 & 3 clinical trials of various drug delivery systems using new technologies such as Solubilizing Nanoparticle technology, Mucus Penetrating Particles technology and Particle Replication In Non-wetting Templates. These new platforms aim to deliver corticosteroids effectively via topical, episcleral, subtenon, oral, and intravitreal routes. Expert opinion: These novel drug delivery platforms have the potential to lead to noninvasive or minimally invasive therapies and may overcome the shortcomings of current pharmacotherapy. However, larger comparative trials are needed for these agents to be added to the current armamentarium in DME management.